A moving contact line as a rheometer for nanometric interfacial layers - Romain Lhermerout (Nature Portfolio, 2016)
The characterisation of interfacial layers, whose rheology can differ from the bulk, is important for the design of new materials. Here, Lhermerout et al. use the dynamics of a moving contact line to quantify the mechanical properties of a polymer thin film.